Development of Tubular Linear Permanent Magnet Synchronous Motor Used in Oil-well Field - Yanliang Xu; Xiquan Liu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
The tubular linear permanent magnet synchronous motor (TLPMSM) is developed to constitute a new oil-well pump system named as linear motor-driven one replacing the normal beam balanced pump system mainly in order to eliminate the damageable steel pole. Its structure is determined based on the real drive demand and the corresponding analysis results are given. At last a small prototyped TLPMSM with stator outer diameter of 140mm, effective stator length of 864mm is designed and manufactured to verify the theoretical analysis and investigate the performance, and make preparation for the large practicable prototype in the future.